On three species of the trapdoor spider Genus Cyclocosmia from China (Araneae, Halonoproctidae) - Yu, Kun; Zhang, Zhi-Sheng (Zootaxa, 2018)
Three trapdoor spiders of the genus Cyclocosmia are photographed, illustrated and described in this paper, including two new species, C. subricketti sp. nov. (male and female) and C. sublatusicosta sp. nov. (male only) from China. The male of C. latusicosta Zhu, Zhang & Zhang, 2006 is described for the first time.